Tracking Drug‐Induced Epithelial–Mesenchymal Transition in Breast Cancer by a Microfluidic Surface‐Enhanced Raman Spectroscopy Immunoassay. Issue 13 (5th March 2020) - Zhang, Zhen; Wang, Jing; Shanmugasundaram, Karthik Balaji; Yeo, Belinda; Möller, Andreas; Wuethrich, Alain; Lin, Lynlee L.; Trau, Matt
Abstract: Epithelial–mesenchymal transition (EMT) is a primary mechanism for cancer metastasis. Detecting the activation of EMT can potentially convey signs of metastasis to guide treatment management and improve patient survival. One of the classic signatures of EMT is characterized by dynamic changes in cellular expression levels of E‐cadherin and N‐cadherin, whose soluble active fragments have recently been reported to be biomarkers for cancer diagnosis and prognosis. Herein, a microfluidic immunoassay (termed "SERS immunoassay") based on sensitive and simultaneous detection of soluble E‐cadherin (sE‐cadherin) and soluble N‐cadherin (sN‐cadherin) for EMT monitoring in patients' plasma is presented. The SERS immunoassay integrates in situ nanomixing and surface‐enhanced Raman scattering readout to enable accurate detection of sE‐cadherin and sN‐cadherin from as low as 10 cells mL −1 . This assay enables tracking of a concurrent decrease in sE‐cadherin and increase in sN‐cadherin in breast cancer cells undergoing drug‐induced mesenchymal transformation. The clinical potential of the SERS immunoassay is further demonstrated by successful detection of sE‐cadherin and sN‐cadherin in metastatic stage IV breast cancer patient plasma samples. The SERS immunoassay can potentially sense the activation of EMT to provide early indications of cancer invasions or metastasis. Abstract : An SERS immunoassay is presented for sensitive and simultaneous detection of the cadherin switch (E/N‐cadherin) in TGF‐β induced epithelial–mesenchymal transition (EMT) in vitro model. The assay is evaluated on stage IV breast cancer patients. The SERS immunoassay might have potential for monitoring EMT activities and early identification of individuals at risk of cancer metastasis.